Expandable porous organic frameworks with built-in amino and hydroxyl functions for CO2 and CH4 capture. Issue 67 (3rd August 2018) - Perego, J.; Piga, D.; Bracco, S.; Sozzani, P.; Comotti, A.
Abstract : Organic functions built on the node of a porous covalent architecture exhibit excellent affinity for CO2 (54 kJ mol −1 ) and CH4 (25 kJ mol −1 ): the interaction of CO2 favorably with amine groups was observed by 2D NMR. Abstract : The synthesis of porous organic 3D frameworks, wherein amine, hydroxyl and Li-alkoxide functions were built directly on the monomer-unit carbon core, realizes improved interactions with target gases. CO2 was retained by the amine group with a remarkable energy of 54 kJ mol −1, while 2D MAS NMR provided rare evidence of amine-to-gas short-distance interactions. Frameworks containing hydroxyl and Li-alkoxide functions show optimal interaction energies with CH4 of up to 25 kJ mol −1 . The light network of 3-branch building units ensures the expandability of the nano-sponges.